2008
DOI: 10.1002/hed.20906
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of 18F‐FDG‐PET/CT for staging of oral squamous cell carcinoma

Abstract: PET/CT scan showed good accuracy in determining the extension and/or depth of invasion of the primary tumor. Nevertheless, PET/CT was not accurate to rule out nodal metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 24 publications
(26 reference statements)
3
31
0
Order By: Relevance
“…Furthermore, as we previously reported (24), in 3 patients 18 F-FDG PET/CT was able to correctly exclude deep-bone involvement detected by CT and MRI, reducing the stage from T4 to T2. In these patients, when comparing the openand closed-mouth scans, we observed that the open-mouth scan allowed an easier restaging of the tumor.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, as we previously reported (24), in 3 patients 18 F-FDG PET/CT was able to correctly exclude deep-bone involvement detected by CT and MRI, reducing the stage from T4 to T2. In these patients, when comparing the openand closed-mouth scans, we observed that the open-mouth scan allowed an easier restaging of the tumor.…”
Section: Discussionsupporting
confidence: 59%
“…Before starting treatment, a key point in diagnosis is to evaluate the presence and extent of tumour invasion into bone. At present, preoperative assessments usually consist of clinical examination, conventional radiography by orthopantomogram (OPG) and periapical radiographs, and if available, computerised tomography (CT), radionuclide bone scanning and magnetic resonance imaging [72]. Other more sophisticated diagnostic tools such as multi-detector row CT or positron emission tomography/CT (PET/CT) have been shown to have a higher sensitivity in the assessment of bone invasion, but are not in routine use in most institutions [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…The use of integrated PET/CECT could have several advantages. In most PET/CT studies, the CT scan portion is a non-optimized head and neck CT and a separate dedicated and fully optimized head and neck CT scan was performed 7,9,23,25 . In this setting PET/CT can cause logistic problems and is time consuming for patient and clinician because of the need to perform an extra imaging modality.…”
Section: Discussionmentioning
confidence: 99%